Kontribusi Kreativitas Siswa dan Fasilitas Labor Terhadap Hasil Belajar Mata Diklat Keterampilan Komputer dan Pengelolaan Informasi (KKPI) Siswa Kelas X di SMK Negeri 1 Tilatang Kamang - Feri Febrianto; Zulwisli Zulwisli; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research is purposed to reveal scales of student’s creativity contribution and laboratorium of facility grade for computer and information management skills subject at X class SMKN 1 Tilatang Kamang. The type of this research is descriptive correlation. Populations in this research are 164 students, and samples are amount to 62 students of X class SMKN 1 Tilatang Kamang, school of year 2012/2013. Samples are taken by simple random sampling technique. Data were collected by questionnaire and documentation. Data analysis technique in this research is Pearson product moment and multiple-correlation. Results from data analysis claimed that there are contributions from learning motivation and learning environment for student’s grade of computer and information management skills subject at X class SMKN 5 Padang, as follow: (1) student’s creativity gives contribution to student’s grade by 14,13%, (2) laboratorium of facility gives contribution to student’s grade by 20.09%, (3) student’s creativity together with laboratorium of facility give contribution to student’s grade by 27,98%. This research suggest that student’s student’s creativity and laboratorium of facility give contribution to student’s grade.Keywords: student’s creativity, laboratorium of facility, student’s grade, descriptive correlation, simple random sampling.